PEMANFAATAN MEDIA AUDIO VISUAL DALAM MENINGKATKAN HASIL BELAJAR LEMPAR CAKRAM GAYA MENYAMPING PADA SISWA KELAS VIII-3 SMP NEGERI 7 MEDAN TAHUN AJARAN 2017/2018 - Tumbur Tamba (Universitas Islam Negeri (UIN) Sumatera Utara, 2020)
This study aims to determine the use of audio-visual media in improving the learning outcomes of side-to-side disc styles. This type of research is classroom action research. The subjects in this study were 32 students of class VIII-3 SMP Negeri 7 Medan. The results of the study concluded: (1) from the first cycle learning outcomes test, it was obtained 18 students with the value after being confirmed (66.60%) had reached the level of learning completeness, while 9 students (33.40%) had not yet reached the level of learning completeness. With the average value of learning outcomes after being confirmed is 68.05. However, it does not meet the expected classical completeness criteria, namely 85%. (2) from the second cycle learning outcomes test, data were obtained as many as 29 students with a value after confirmation of (88.88%) who had achieved mastery in learning and 3 students (11.12%) were still incomplete.